Breakthrough COVID-19 infections – Analyzing our experience - Hussain, Aneela; Sarfaraz, Samreen; Anis, Sabiha; Shaikh, Quratulain; Rahim, Anum; Behram, Shameem; Shah, Rabeea; Khan, Owais (Pakistan Journal of Medical Sciences, 2023)
Objective: There are many cases of post-vaccination COVID-19 globally. Also, literature on serum antibodies after vaccination is abundant. Our research focuses on breakthrough infections reported at our institution during the third wave of COVID-19.Methods: A total of 177 people recruited at the Indus Hospital Karachi between May to September 2021 with COVID-19 infection were divided into vaccinated, partially vaccinated, and unvaccinated cohorts. Furthermore, a subset of the vaccinated cohort was tested for anti-NP and anti-S antibodies.Results: There were 119 patients with breakthrough infection, however, 74% had mild symptoms. The antibodies against NP and S were found at a higher level in those who had a breakthrough infection in comparison to healthy vaccinated controls.Conclusion: Vaccination does not prevent disease but does confer some immunity causing less severe infection.doi: https://doi.org/10.12669/pjms.39.5.6724How to cite this: Hussain A, Sarfaraz S, Anis S, Sheikh Q, Rahim A, Behram S, et al. Breakthrough COVID-19 infections – Analyzing our experience. Pak J Med Sci. 2023;39(5):1225-1231. doi: https://doi.org/10.12669/pjms.39.5.6724This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.